The Experience of SMA Negeri 1 Babat Students Using DeepSeek to Form Multicultural Character: A Phenomenological Study - Fa'ieq Firmansyah Bimantara; Khotimatus Sholikhah; Sulhatul Habibah (Yayasan Rahmat Islamiyah, 2026)
This study aims to understand the experiences of students at SMA Negeri 1 Babat in utilizing the AI platform DeepSeek as a learning medium to develop multicultural character. The research employs a qualitative approach with a phenomenological study design to interpret students’ learning experiences in depth. Data were collected through observation, in-depth interviews, and reflections on students’ learning experiences while using DeepSeek in educational activities. Data analysis was conducted using the Interpretative Phenomenological Analysis (IPA) approach to identify emerging themes from participants’ narratives. The results indicate that DeepSeek functions as a medium for self-reflection, a tool to broaden cultural insights, and a space for simulating cross-perspective dialogue that fosters tolerance, empathy, and openness among students toward diversity within the school environment, as well as strengthening multicultural awareness in students’ social interactions. Therefore, the use of DeepSeek as an AI-based learning medium is proven to support the development of students’ multicultural character in a reflective and contextual manner.